Thioacetamide-Induced Acute Hepatic Encephalopathy in Rat: Behavioral, Biochemical and Histological Changes - Farjam, M (Kowsar, 2012)
BACKGROUND: As a serious neuropsychiatric disease, hepatic encephalopathy (HE) is a clinical condition with several types regarding chronicity and clinical diversity that can develop as a complication of both acute and chronic liver failure. This study evaluates changes in thioacetamide (TAA)-induced acute hepatic encephalopathy (AHE) in rat as an animal model. METHODS: Both genders of C57BL6, BALB/C mice and Sprague Dawley rats; (10 animals in each group) were compared for induction of AHE to clarify which animal and gender were appropriate. The animals (10 male rats in each group) were categorized in 4 groups according to the dose of the TAA administered (200, 300 and 400 mg/kg of TAA at 24 h intervals for 4 days). A control group was treated with solvent of TAA which was water (5 ml/kg/day). The behavioral, biochemical markers of hepatic failure and histological aspects of thioacetamide (TAA) induced AHE and the correlation between the clinical severity and liver failure biomarkers were evaluated. RESULTS: Rat was shown to be an animal model of choice for AHE while the optimum dosage of TAA to induce AHE was 300 mg/kg/day at 24 h intervals for 4 days. The behavioral score was partially correlated with the rising of some biomarkers and pathological findings. CONCLUSION: Rat can be introduced as the animal of choice for AHE to study the pathophysiology, pharmacology and the survival rate of disease in liver transplant patients.